Destabilizing digital "bank walks" - Naz Koont; Tano Santos; Luigi Zingales (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2023)
We study the impact of digital banking on the value of the deposit franchise and the stability of the banking sector. Using the classification of digital banking in Koont (2023), we find that when the Fed funds rate increases deposits flow out faster and the cost of deposits increases more in banks with a digital platform. The results are similar for insured and non-insured deposits. Using the model of Drechsler et al. (2023c), we find that correcting for digital betas and deposit outflows results in a deposit franchise value that is 40% lower for digital-broker banks relative to a traditional bank without digital platform. We apply this analysis to Silicon Valley Bank (SVB) and find that the reduced value of the deposit franchise explains why SVB was insolvent in early March 2023, even before the bank run occurred.
Keywords: 330